DUSP12 acts as a novel endogenous protective signal against hepatic ischemia–reperfusion damage by inhibiting ASK1 pathway. Issue 1 (15th January 2021) - Boldorini, Renzo; Clemente, Nausicaa; Alchera, Elisa; Carini, Rita
Abstract: Ischemia–reperfusion injury (IRI) consequent to major liver surgery is a still unmet clinical problem. The activation of endogenous systems of hepatoprotection can prevent the damaging effects of ischemia–reperfusion (IR) as shown by the phenomenon known as 'ischemic preconditioning'. The identification of endogenous signal mediators of hepatoprotection is of main interest since they could be targeted in future therapeutic interventions. Qiu et al. recently reported in Clin. Sci. ( Lond. ) (2020) 134 (17), 2279–2294, the discovery of a novel protective molecule against hepatic IR damage: dual-specificity phosphatase 12 (DUSP12). IR significantly decreased DUSP12 expression in liver whereas DUSP12 overexpression in hepatocytes protected IRI and DUSP12 deletion in DUSP12 KO mice exacerbated IRI. The protective effects of DUSP12 depended on apoptosis signal-regulating kinase 1 (ASK1) and acted through the inhibition of the ASK1-dependent kinases c-Jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinase (MAPK). These results enlighten DUSP12 as a novel intermediate negative regulator of the pro-inflammatory and pro-apoptotic ASK1/JNK-p38 MAPK pathway activated during hepatic IR and identify DUSP12 as potential therapeutic target for IRI.